Complementary and alternative medicine use among children with mental health issues: results from the National Health Interview Survey - Claudia Wang; John Preisser; Yunro Chung; Kaigang Li (BMC, 2018)
Abstract Background Mental health issues in children have become a serious public health concern in the U.S. within the past few decades. Emerging evidence suggests that Complementary and Alternative Medicine (CAM) can be beneficial for various mental health issues. However, little is known about the prevalence, reasons, and associated factors of CAM use among this population in the U.S. The purpose of this study is to examine the characteristics of CAM use among U.S. children with mental health issues. Methods Utilizing the 2012 National Health Interview Survey data, we used descriptive analysis, Wald F-statistics, and multivariable survey logistic regression models to examine the prevalence, patterns, and associated factors of CAM use in children aged 4-17 (n = 10,233) adjusting for the complex sampling design. Results CAM use is more popular among children with mental health issues compared with those without (19.2% vs. 10.1%, p < 0.001). Herbal remedies (9.1%), mind-body therapies (5.5%), and chiropractic care (5.3%) were the most frequently used modalities. Primary reasons for children to use CAM are because they are helpful (69.2%), natural (55.9%), and holistic (44.7%). The majority of CAM users perceived CAM therapies are helpful. Predictors of CAM use are children who are female, whose parents had a higher educational level and socioeconomic status, and who had at least one co-morbid medical condition. Only 18.4% of CAM usage was recommended by medical doctors. Conclusions Approximately 10 million parents of children with mental health issues reported the use of CAM therapies, mainly because of their desire for a more natural and holistic healthcare approach. Given that the majority of CAM users perceived CAM therapies as helpful, future studies should investigate the unique contributions of CAM in pediatric psychiatric care. Because a low percentage of CAM use was recommended by medical doctors, educational interventions designed to equip medical professionals with CAM knowledge and experience will be conducive to improving effective patient-physician communication in clinical settings. Since CAM use is reported as more prevalent by parents' of children with higher education and family income, effective strategies designed to reduce disparities in accessing promising CAM therapies are warranted.